2006
DOI: 10.2478/s11535-006-0017-3
|View full text |Cite
|
Sign up to set email alerts
|

Proteasome activity in experimental diabetes

Abstract: Numerous studies have indicated that oxidative stress contributes to the development and progression of diabetes and other related complications. Since the ubiquitin-proteasome pathway is involved in degradation of oxidized proteins, it is to be expected that alterations in proteasomedependent proteolysis accompany diabetes. This paper focuses on the role of the proteasome in alloxaninduced experimental diabetes. The changes in proteasomal activity and oxidative stress indices (protein oxidation and lipid pero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Proteolytic inactivity in proteasomes was a direct consequence of oxidative stress or a result of other diabetes‐related metabolic alterations, assigning a definite role for proteasomal activities in the genesis and progression of diabetic cardiac complications. The ubiquitin–proteasome system becomes dysfunctional during long‐term hyperglycaemia . In earlier studies, we and others showed that cardiac 4HNE levels were increased in both type 1 and type 2 diabetes .…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations
“…Proteolytic inactivity in proteasomes was a direct consequence of oxidative stress or a result of other diabetes‐related metabolic alterations, assigning a definite role for proteasomal activities in the genesis and progression of diabetic cardiac complications. The ubiquitin–proteasome system becomes dysfunctional during long‐term hyperglycaemia . In earlier studies, we and others showed that cardiac 4HNE levels were increased in both type 1 and type 2 diabetes .…”
Section: Introductionmentioning
confidence: 83%
“…First, increased 4HNE adduct formation with the mitochondrial respiratory complex 2 protein succinate dehydrogenase was reported in the heart tissue by Lashin et al . Second, 4HNE‐induced mitochondrial damage in the diabetic heart has been widely reported; however, only a few studies determined the role of 4HNE in other subcellular organelles like the proteasome in diabetic cardiomyopathy …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The chymotrypsin-like enzyme rather than trypsin-like protease contributes to the yield of hemorphins since their cleavage sites contained hydrophobic residues. The changes of proteasomal activity in alloxan-induced experimental model of diabetes are studied [11]. The results indicate a significantly decreased chymotrypsinlike activity, increased trypsin-like activity and unaltered peptidylglutamyl peptide-hydrolyzing activity.…”
mentioning
confidence: 99%